A Multimode Power Processor With Wired and Wireless Battery Charging for Electric Vehicle - Meher S.R.; Singh R.K. (My University, 2025)
The propulsion unit is the prime power module in an electric vehicle (EV) that keeps it moving. This module includes a propulsion motor and a power electronic interface that converts dc to three phase ac for driving the motor. In addition to this, separate power electronic modules are used for on-board wired charging and wireless charging. This article proposes a multimode power processor for EV capable of serving the purpose of three different power modules required for propulsion, wired charging, and wireless charging. This optimizes the weight, volume, and cost of the EV as separate power modules are avoided for three different modes. This article also proposes a new scheme for the transmitting side power electronic module that taps power from the single-phase utility grid and generates high frequency ac using a resonant inverter for wireless power transfer. In both the wired and wireless charging method, the proposed technique draws power from the single-phase wall outlet, charges the EV battery pack with constant current-constant voltage charging logic and performs power factor correction operation at the input ac grid side. A laboratory scale prototype is developed for experimentally validating the proposed concept with a 24 V, 30 Ah battery set and a 24 V, 400 W BLdc motor. © 1982-2012 IEEE.